Model for innovative organizational culture in coffee growers in Cesar State, Colombia - Pertuz-Peralta, Vanessa; Perez-Orozco, Adith Bismarck (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper aims to propose a new model for the development of an organizational innovative culture in the business sector. The model is inspired by the analysis of the Asociación de Productores Orgánicos Arhuacos y Campesinos de la Sierra Nevada de Santa Marta, Asoprocasines. This study is developed based on the qualitative approach, and it is validated by a case study. The data are recollected by direct observation, using an analysis matrix. The proposed model integrates the determinants factors in the generation of an innovative culture, based on the review of the literature. This model defines five steps: joint innovation to competitive strategy, developing skills in staff, customer feedback, planning and monitoring of innovation strategies, and monitoring the actions and strategies. The culture of change and the interaction of the company with the external environment are discussed. Additionally, two driving forces of this process are included, which are the adoption of culture of change and the interaction between company and external environment. Also, the model relies on the steps for managing innovation planed by the COTEC Foundation in 2004.